Heutagogy As A Modern Concept Of Self-Education - Topuzyan, Aida; Poghosyan, Lusine; Harutyunyan, Gayane (Զանգակ հրատ.)
In today's rapidly changing world, a person must constantly update his knowledge in order to keep up with the times. Self-education today is seen as the key to success and satisfaction in life. Nowadays, self-education leads to transformation, which is one of the important factors in new opportunities and career growth. A world that is constantly evolving has made it possible to develop a new pedagogical branch of self-education - heutagogy. Heutagogy is based on the following conceptual statement important for modern society: "knowledge not for the whole life, but knowledge during the whole life".
Keywords: Education